Penerapan Teknologi Steam Bending Untuk Efisensi Bahan Baku Kayu IDesign Furniture di Desa Bawu Kecamatan Batealit Kabupaten Jepara - Achmad Zainudin; Nur Aeni Widiastuti; Noor Nailie Azzat (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Jepara Regency is a famous city of carving and furniture industries. One player of this industries is MSMEs IDesign Furniture located in Bawu village, Batealit subdistrict as our partner in this community service activity which Nova Elisyana as the owner since 2017 and curved chairs also tables as their products. The large market demand for curved chair products can cause problems in aspects of the production process such as: 1) increasingly scarce raw materials and rising prices, 2) Wrong techniques in curving wood resulting in production failures, 3) lack of communication between buyers and furniture owner, in marketing aspect makeshift promotional media with product displays in the showroom. Therefore, the aim of this community service is training in wood bending technical skills using steam bending technology so more efficiently in using raw material while producing curved chairs, for marketing aspect providing digital marketing training as a more effective promotional medium. The results are 1) increasing technical skills wood bending with steam bending technology on produce curved chairs for IDesign Furniture in particular and training participants in general, 2) increasing skills in selecting types of wood as the raw material for curved chairs, 3) Draft design drawing Redesigning the Layout of Production Facilities on the factory floor and machines, 4) for marketing aspect the results are one website and Instagram optimization, 5) improving the maintenance of the IDesign Furniture website.